Killer whales (Orcinus orca) in Iceland show weak genetic structure among diverse isotopic signatures and observed movement patterns. Issue 23 (14th November 2018) - Tavares, Sara B.; Samarra, Filipa I. P.; Pascoal, Sonia; Graves, Jeff A.; Miller, Patrick J. O.
Abstract: Local adaption through ecological niche specialization can lead to genetic structure between and within populations. In the Northeast Pacific, killer whales ( Orcinus orca ) of the same population have uniform specialized diets that are non‐overlapping with other sympatric, genetically divergent, and socially isolated killer whale ecotypes. However, killer whales in Iceland show intrapopulation variation of isotopic niches and observed movement patterns: some individuals appear to specialize on herring and follow it year‐round while others feed upon herring only seasonally or opportunistically. We investigated genetic differentiation among Icelandic killer whales with different isotopic signatures and observed movement patterns. This information is key for management and conservation purposes but also for better understanding how niche specialization drives genetic differentiation. Photo‐identified individuals ( N = 61) were genotyped for 22 microsatellites and a 611 bp portion of the mitochondrial DNA (mtDNA) control region. Photo‐identification of individuals allowed linkage of genetic data to existing data on individual isotopic niche, observed movement patterns, and social associations. Population subdivision into three genetic units was supported by a discriminant analysis of principal components (DAPC). Genetic clustering corresponded to the distribution of isotopic signatures, mtDNA haplotypes, and observed movement patterns, but genetic units were not socially segregated. Genetic differentiation was weak ( F ST < 0.1), suggesting ongoing gene flow or recent separation of the genetic units. Our results show that killer whales in Iceland are not as genetically differentiated, ecologically discrete, or socially isolated as the Northeast Pacific prey‐specialized killer whales. If any process of ecological divergence and niche specialization is taking place among killer whales in Iceland, it is likely at a very early stage and has not led to the patterns observed in the Northeast Pacific. Abstract : Killer whales in Iceland show intrapopulation variation of isotopic niches and, while some individuals appear to specialize on herring and follow it year‐round, others feed upon herring only seasonally or opportunistically. We investigate the level of genetic differentiation within the population using a multivariate clustering technique and existing data on individual isotopic niche, observed movement patterns and social association for 61 genotyped photo‐identified individuals. Spatial clustering based on microsatellites identified three genetic units that were not socially segregated and corresponded to differences in isotopic signatures, mitochondrial haplotypes and observed movement patterns, but genetic differentiation was weak ( F ST < 0.1) suggesting ongoing gene flow or recent separation of the genetic units.